Theoretical rheological models for olive oil - Stanciu, Ioana (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This paper proposes new rheological models for olive oil. The purpose of this study was to find an exponential dependence between temperature and dynamic viscosity of olive oil, using one equation. Equation constants ln?0, A1 and t1 were determined by fitting exponential. The olive oil have investigated using a Haake VT 550 Viscotester developing shear rates ranging between 3 and 120 s-1 and measuring viscosities from 104 to 106 mPa·s when the HV1 viscosity sensor is used. Olive oil dynamic viscosity decreases with increasing temperature at constant shear rate. Plotting the ln dynamic viscosity depending on temperature shows an exponential decline.